ARTISTIC INTERPRETATION OF THE THEME OF THE MOTHERLAND IN POETRY (American Journal of Research in Humanities and Social Sciences, 2023)
Literary interpretation of the theme of Motherland in poetry has been a source of inspiration and thought for readers and scholars throughout history. Poets often explore the themes of spirituality, faith and divine love and express their feelings and understanding of divine love through the middle of the verse.